Extraction of Exosomes from Glioblastoma Multiforme Patients’ Blood Plasma - I. F. Gareev; O. A. Beylerli; Sh. Zhao; G. Yang; J. Sun; A. T. Beilerli; Sh. M. Safin (Креативная хирургия и онкология)
Introduction. Glioblastoma multiforme (GBM) is the most common and aggressive form of primary malignant brain tumour in adults associated with a poor prognosis. Exosomes have been shown to be useful non-invasive biomarkers for the diagnosis and prognosis of tumours, GBM included. Exosomes play a role of biological carriers which can perform various tasks through various signalling pathways of carcinogenesis, such as PI3K/AKT, SOX2, PTEN, ERK and STAT3.Materials and methods. Exosomes were isolated from blood plasma taken from patients diagnosed with GBM prior to surgical resection.Results and discussion. Plasma exosomes from patients with GBM had spherical shape and varied in size from 40 to 100 nm matching the exosomes’ morphological characteristics. The combination of ultrafiltration and double ultracentrifugation makes it possible to extract exosome examples from plasma without the presence of contaminating particles over 100 nm in size; the shape and size of these vesicles match the characteristics of exosomes isolated from other biological fluids.Conclusion. The experimental protocol for the extraction of exosomes from GBM patients’ plasma described here proves effective as a method used to ensure the purity of exosomes. Applying this method offers further opportunities for research into the role of exosomes in GBM pathogenesis. Equally this method can be used in research involving other human pathologies.